(untitled) (Research, Society and Development, 2022)
With annual production of approximately 700 thousand tons, Brazil stands out as the world’s largest producer of passion fruit. Although production takes place mainly in the Northeast region of the country, production in the Amazon region – Amazonas, Pará and Rondônia – is also noteworthy. Therefore, the present study aimed to determine and evaluate the productivity of passion fruit (Passiflora Edulis) in the central region of Rondônia - Western Amazon, Brazil. For this, it was necessary to carry out a descriptive and exploratory research, as well as a bibliographic research and a field study, using semi-structured interviews for data collection. The data collected from 37 (thirty seven) passion fruit producers who grow the fruit in the Western Amazon/Brazil - central region of the state of Rondônia, were treated qualitatively and quantitatively. Thus, it was found that there was an average production of 11.14 tons per hectare in the analyzed period, equivalent to 13.70 tons per hectare/year. Concerning the Pearson correlation analysis performed, the average dependence of productivity with the practice of technical assistance (with or without technical assistance) stands out. Additionally, it was investigated and noticed that the producers who had technical assistance in the period, perceived a production 97.75% higher than the average production in the region (average of 22.03 tons/ha against 11.14 tons/ha). Therefore, it is inferred that investment in technical assistance is one of the possibilities for increasing passion fruit productivity in the central region of Rondônia - Western Amazon.